2020
DOI: 10.3390/ijerph17030768
|View full text |Cite
|
Sign up to set email alerts
|

City of Hope Quality of Life-Ostomy Questionnaire Validity and Reliability Assessment on a Croatian Sample

Abstract: The aim of this study was to validate City of Hope Quality of Life-Ostomy Questionnaire (CoH-QoL-OQ) for assessing the quality of life (QoL) of ostomy patients in the Republic of Croatia. The CoH-QoL-OQ is widely used, but has not been translated or validated so it can be used in the Republic of Croatia. This cross-sectional study encompassed 302 surgery patients with colostomy, ileostomy, or urostomy (182 (60.3%) male and 120 (39.7%) female), whose average age is 59 (M = 59.3, SD = 15.8). The CoH-QoL-OQ was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 24 publications
6
10
1
Order By: Relevance
“…About this, a Persian study has shown that the QOL was 6.37 (±1.66). A divergent result was observed in the present study in which physical well-being was the highest, and then the spiritual, psychological, and social dimensions (Konjevoda et al, 2020).…”
Section: Discussioncontrasting
confidence: 95%
“…About this, a Persian study has shown that the QOL was 6.37 (±1.66). A divergent result was observed in the present study in which physical well-being was the highest, and then the spiritual, psychological, and social dimensions (Konjevoda et al, 2020).…”
Section: Discussioncontrasting
confidence: 95%
“…4 Numerous studies have reported that all domains of quality of life were significantly influenced by ostomy-related problems, with social well-being being the most strongly affected domain. 28 , 32 , 33 Our finding indicating that social well-being was the most problematic area of quality of life is consistent with previous studies conducted in Iranian, 32 Chinese, 33 Croatian, 28 and even Korean 34 CRC patients with ostomies. Similar to a 2020 study by Konjevoda and colleagues, 28 our results highlighted poorer outcomes for patients’ psychological and social well-being compared with their physical and spiritual well-being.…”
Section: Discussionsupporting
confidence: 92%
“…Quality of life was assessed using the City of Hope Quality of Life–Ostomy that has been widely used in clinical studies with high reliability and validity. 27 , 28 This instrument consists of three sections. The first part contains 13 questions used to assess demographic, disease, and ostomy-specific characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…First, our study sample was considerably older than those in other studies of stoma-related QoL ( Anaraki et al, 2012 ; Cotrim & Pereira, 2008 ; Dhamnaskar et al, 2019 ; Konjevoda et al, 2020 ; Liao & Qin, 2014 ; Yilmaz et al, 2017 ), and our modeling showed that older age was independently associated with better QoL. The older median age of our sample likely reflects the demographic characteristics of the study setting, as there is a higher proportion of people aged 65 years and older living in inner and outer regional areas of Australia ( AIHW, 2019 ).…”
Section: Discussionmentioning
confidence: 97%